Separation and Enrichment of Lectin from Zihua Snap-Bean (Phaseolus vulgaris) Seeds by PEG 600–Ammonium Sulfate Aqueous Two-Phase System - Jiang, Bin (Molecules, 2017)
A fast and efficient method based on a polyethylene glycol (PEG) 600/(NH(4))(2)SO(4) aqueous two-phase system for extracting lectin from Zihua snap-bean (Phaseolus vulgaris) seeds was established. According to a Box–Behnken design (BBD), involving four factors at three levels each subjected to analysis of variance (ANOVA) and response surface analysis, the protein recovery and the purification factor of lectin in the top phase were used as the response values of the variance analysis to acquire the multivariate quadratic regression model. SDS–PAGE electrophoresis and the hemagglutination test were used to detect the distribution of lectin in the aqueous two-phase system (ATPS). The obtained data indicated that lectin was preferentially partitioned into the PEG-rich phase, and the ATPS, composed of 15% (NH(4))(2)SO(4) (w/w), 18% PEG 600 (w/w), 0.4 g/5 g NaCl and 1 mL crude extract, showed good selectivity for lectin when the pH value was 7.5. Under the optimal conditions, most of the lectin was assigned to the top phase in the ATPS, and the hemagglutination activity of the purified lectin in the top phase was 3.08 times that of the crude extract. Consequently, the PEG 600/(NH(4))(2)SO(4) aqueous two-phase system was an effective method for separating and enriching lectin directly from the crude extract of Zihua snap-bean seeds.